Faludi Blogging Chasing Territorialism - Faludi, Andreas (TU Delft Open, 2022)
"Chasing Territorialism" gathers short texts by Emeritus Professor Andreas Faludi, originally written as blog posts over a period of two years. In Andreas' words: "Stimulated by an, albeit brief, encounter with Albania celebrating Europe Day, I began blogging about the continuing relevance of criticising territorialism, as I'd done in The Poverty of Territorialism (Faludi 2018; Edgar Elgar), in particular - but not exclusively - in relation to European integration." Here, territorialism stands for states claiming a monopoly on controlling their territories much as they try to control the loyalty of their citizens. As such, territorialism is a fundamental principle of political organisation. Continued reflection on the poverty of this principle has acquired urgent overtones with the resurgence of armed conflict in Europe and elsewhere. If anything, the general reaction to this and other continental and even global crises seems to be to further enforce territorialism. But, what if territorialism is the cause of, rather than the solution to our problems? If so, would heeding the call for determined state action not become a case of: 'Out of the frying pan and into the fire'? This book does not give an answer. What it hopefully does is stimulate debate about what the answer should be.